Triple-Columned and Multiple-Layered 3D Polymers: Design, Synthesis, Aggregation-Induced Emission (AIE), and Computational Study - Guanzhao Wu; Yangxue Liu; Zhen Yang; Liulei Ma; Yao Tang; Xianliang Zhao; Hossein Rouh; Qixuan Zheng; Peng Zhou; Jia-Yin Wang; Farhan Siddique; Sai Zhang; et al. (Research, 2021)
Conjugated polymers and oligomers have great potentials in various fields, especially in materials and biological sciences because of their intriguing electronic and optoelectronic properties. In recent years, the through-space conjugation system has emerged as a new assembled pattern of multidimensional polymers. Here, a novel series of structurally condensed multicolumn/multilayer 3D polymers and oligomers have been designed and synthesized through one-pot Suzuki polycondensation (SPC). The intramolecularly stacked arrangement of polymers can be supported by either X-ray structural analysis or computational analysis. In all cases, polymers were obtained with modest to good yields, as determined by GPC and 1H-NMR. MALDI-TOF analysis has proven the speculation of the step-growth process of this polymerization. The computational study of ab initio and DFT calculations based on trimer and pentamer models gives details of the structures and the electronic transition. Experimental results of optical and AIE research confirmed by calculation indicates that the present work would facilitate the research and applications in materials.